Infection by Mycoplasma spp., feline immunodeficiency virus and feline leukemia virus in cats from an area endemic for visceral leishmaniasis - Marcondes, Mary [UNESP]; Hirata, Karina Y. [UNESP]; Vides, Juliana P. [UNESP]; Sobrinho, Ludmila S. V. [UNESP]; Azevedo, Jaqueline S. [UNESP]; Vieira, Thállitha S. W. J.; Vieira, Rafael F. C. (My University, 2018)
Background: Visceral leishmaniasis (VL) has been increasingly recognized in cats living in areas endemic for the disease. Co-infection with Leishmania infantum and other infectious agents is well established in dogs. However, for cats, data on co-infections with L. infantum and other infectious agents are still sparse. The aim of this study was to identify the prevalence of vector-borne pathogens, Mycoplasma spp., feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) in cats from an area endemic for VL in southeastern Brazil. Results: Of the 90 cats, eight (8.9%) were infected with Mycoplasma spp., five (5.5%) were FIV- positive and one (1.1%) was FeLV-positive. Co-infection with L. infantum and at least one other infectious agent was found in 9/50 (18.0%; CI: 8.6-31.4%) cats. In Group 1 (cats infected naturally by L. infantum), 4/50 (8.0%) cats were positive for FIV, 4/50 (8%) for Mycoplasma spp. and 1/50 (2.0%) was co-infected with FeLV and Mycoplasma spp. In Group 2 (cats non-infected with L. infantum), 2/40 (5.0%) cats were infected with Mycoplasma spp. and 1/40 (2.5%) was co-infected with FIV and Mycoplasma spp. All cats were negative for Ehrlichia spp., Babesia spp. and Anaplasma platys. Conclusion: A low prevalence of co-infection in Leishmania-infected and non-infected cats was found. Co-infections with Leishmania and vector-borne diseases in cats are not common in this area endemic for VL in Brazil.
Keywords: Anaplasma platys; Babesia spp.; Ehrlichia spp.; Leishmania infantum; PCR